The role of platform quality and publicly owned platforms in the free-to-air broadcasting industry - Miguel González-Maestre; Francisco Martínez-Sánchez (SERIEs - Journal of the Spanish Economic Association, 2014)
In this study, we consider the role of a publicly owned platform and programme quality in the free-to-air broadcasting industry. We compare the equilibrium levels of advertising under private and mixed duopoly competition, and show that the connection between programme quality and advertising incentives is drastically different in each scenario. We also consider the welfare implications of our analysis and generate policy implications regarding the optimal level of government intervention in the broadcasting industry.
Keywords: L11; L33; L82; M37; 330; Quality; Mixed duopoly; Advertising; Media